Fast transient control for power adjustment in a dual‐active‐bridge converter. Issue 16 (1st August 2017) - Lin, S.‐T.; Li, X.; Sun, C.; Tang, Y.
Abstract : A transient control for a dual‐active‐bridge (DAB) dc/dc converter to realise power adjustment in a fast and smooth way is proposed. The converter is able to transfer power between two dc sources with two phase‐shifts as control variables. To eliminate the possible high‐current overshoot and non‐zero dc‐bias current, the adjustments of the two phase‐shifts are distributed to the gating signals of different switch arms according to a ratio x, which has an universal expression for any transitions among different operation modes in a DAB converter. Experimental results have proved the validity of the proposed transient control in elimination of current overshoot and dc‐bias current.